Cmaptools y su aporte en el aprendizaje de los estudiantes del bachillerato técnico en informática de la Unidad Educativa Emigdio Esparza Moreno, Periodo Académico octubre 2024 - marzo 2025. - Amaya Camacho, Guillermo Rolando (2025)
This research work focuses on Cmaptools and its contribution to the learning of students of the Technical Baccalaureate in Computer Science of the Emigdio Esparza Moreno Educational Unit, academic period October 2024 - March 2025. The main objective is to analyze how Cmaptools contributes to learning, using a mixed methodology that combines qualitative and quantitative research. Surveys were applied to students to collect data on their experience with said platform, allowing for evolution at a local level. The research highlights that Cmaptool, as a visual and collaborative tool, can improve students' motivation and academic performance. Problems such as lack of interest and low grades were identified, which traditional methodologies fail to adequately address. Cmaptool allows students to organize ideas and collaborate in real time, facilitating active learning and the understanding of complex concepts. The results indicated a high percentage of students consider that Cmaptools favors their educational process. It is concluded that this platform not only improves information retention, but also fosters critical skills such as critical thinking and problem solving, essential in their technical training. In summary, Cmaptools is presented as an innovative tool that transforms learning by adapting to the individual needs of students